Comunicação, consumo e educação: os discursos sobre ciência na telenovela Morde & Assopra uma aventura interdisciplinar sobre aprender, apreender, ouvir e contar histórias - Antonacci, Andrea Celeste Montini (2013)
The narratives about science shown in the Morde & Assopra TV Novel, and Caçadora de Dinossauros (Dinosaur Hunter) blog, present in the plot, are key to analyzing the consumption of such discourses and their redefinition by students of the Elementary School. Morde & Assopra aired in 2011 at 7 p.m. by Globo TV (broadcast TV and audience leader). Its plot highlights the universe of scientific work: the main character, Julia (Adriana Esteves) is a paleontologist, and Caçadora de Dinossauros her Dinosaur Hunter blog brings texts on paleontology. We aim our analysis in proposing new ways of narrating emerging from the intersection of television and the Internet. We aim to further verify identity constructions arising from mediatized society that, at present, is also pervaded by a culture of interactive digital communication. Another purpose is to detect the cognitive process in a scenario of technological convergence. Specifically for this element, we propose to build a blog by students participating in the study. We anchor our study in mediations such as: Technicality, Identity, Rituality and Cognition, proposed by Jesús Martín-Barbero. Our methodology blends quantitative and qualitative research, including action-research activity in the classroom.